Multiscale Modeling-Based Assessment of Elastic Properties of SLGS-Polymer Nanocomposites with Double-Atom Vacancy Defects - Wang, Z.Q.; Yu, Z.W.; Sun, X.Y.; Li, H.; Wang, Y.J. (Проблемы прочности, 2018)
In this study, which is a continuation of our earlier work, the effect of double-atom vacancy defects (DAVD) on the elastic properties of single-layered graphene sheets (SLGS)-polymer nanocomposites is assessed by the multiscale modeling. According to the latter approach, the polymer matrix is modeled by finite element approach, while the SLGS and interphase layer are simulated at the atomistic scale by the molecular structural mechanics approach. In view of the Lennard–Jones potential concept, it is assumed that the SLGS and polymer matrix are related by van der Waals reciprocity. The fact that the elastic modulus of a polymer with 5% volume fraction of SLGS is increased by 17 times is demonstrated by numerous simulation results. It is also shown that the elastic modulus of SLGS-polymer nanocomposites with DAVDs is deteriorated with an increase in the number of DAVDs and improved with the increased volume fraction of SLGS.